Method for solvent-free in-situ coating of lithium battery positive electrode material
Through the solvent-free in-situ coating method, polyurethane monomer reacts with the positive electrode material at room temperature to form a coating, solving the problems of complexity of traditional coating methods and environmental pollution, achieving efficient positive electrode material coating, and extending the cycle life of lithium batteries.
Patent Information
- Application Number
- CN202311217730.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-03-21
AI Technical Summary
The traditional lithium battery positive electrode material coating method requires the use of solvents, which leads to complex processes, environmental pollution and high costs, making it difficult to adapt to large-scale industrial production.
By using the solvent-free in-situ coating method, polyurethane coating is formed and coated on the surface of the positive electrode material by mixing the polyurethane monomer with the positive electrode material particles and reacting at room temperature.
This method simplifies the process flow, reduces the use of solvents, improves the coating effect, inhibits the volume expansion and side reactions of the positive electrode material during charging and discharging, and extends the cycle life of the lithium battery.
Smart Images

Figure CN119674071A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium batteries, and in particular, relates to a method for solvent-free in-situ coating of lithium battery positive electrode materials. Background Art
[0002] Lithium batteries have driven the development of consumer electronics and electric vehicles. At the same time, as consumers' demand for lithium battery range increases, lithium batteries are facing continuous technological upgrades. The improvement of battery energy density depends on the optimization of electrode materials. Considering resource factors, environmental factors, battery costs and the energy density of positive electrode materials, lithium battery positive electrode materials are rapidly shifting to high nickel and low cobalt. This type of material has the advantage of high energy density, but it also has problems such as large volume expansion of the crystal structure, metal ion dissolution, and lattice oxygen evolution. In this context, surface coating of positive electrode materials is largely regarded as an effective method to optimize the electrochemical performance of positive electrode materials.
[0003] The cathode surface coating is an artificial physical barrier formed on the surface of the electrochemically active cathode particles. The main function of such coatings is to act as a protective passivation film to prevent direct contact between the cathode material and the electrolyte, thereby mitigating harmful side reactions that may reduce battery performance. Ideally, the coating should be thin and have better ionic and electronic conductivity than the cathode material. A good coating can also enhance the charge transfer between the cathode material and the electrolyte, while providing an electron percolation path between the cathode material and the current collector. However, traditional coating coating methods usually require the use of solvents to disperse the polymer so that the coated polymer material is evenly distributed on the surface of the cathode material. This type of method has cumbersome preparation processes, complex experimental processes, and excess solvents will have adverse effects on human health and environmental pollution, and is not suitable for large-scale modification of lithium battery cathode materials. Summary of the invention
[0004] The present invention aims to provide a method for solvent-free in-situ coating of lithium battery positive electrode materials. The obtained coating layer can effectively inhibit the volume expansion of positive electrode material particles during charging and discharging and the side reaction between positive electrode particles and electrolyte, thereby improving the cycle life of lithium batteries.
[0005] In order to achieve the above object, the present invention provides a method for solvent-free in-situ coating of a positive electrode material, comprising the following steps:
[0006] 1) Two monomers, polyol or polyamine, and polyisocyanate used to prepare polyurethane are mixed with positive electrode particles respectively, so that the two monomers are distributed on the positive electrode material particles;
[0007] 2) The positive electrode active material particles dispersed with the two monomers are mixed, so that the two monomers on the positive electrode material react with each other while adhering to the surface of the particles, thereby preparing a positive electrode material with a polyurethane coating.
[0008] According to an embodiment of the present invention, the two monomers polyol or polyamine and polyisocyanate used to prepare polyurethane in step 1) can react at 0-40°C, that is, all polyurethane monomers polyol or polyamine and polyisocyanate that can react at 0-40°C can be used as monomers of the present invention.
[0009] The polyol, polyamine and polyisocyanate may have two or more functional groups, for example 2-5, preferably 2 or 3.
[0010] The polyol and polyamine are preferably polyols or polyamines having siloxane segments, including but not limited to at least one of bisamino-terminated siloxane, bisamino-terminated polysiloxane (e.g., aminopropyl bisamino-terminated polydimethylsiloxane), bishydroxy-terminated siloxane, and bishydroxy-terminated polysiloxane. The average molecular weight of the bisamino-terminated polysiloxane and the bishydroxy-terminated polysiloxane is greater than 1000, for example, 1000-30000, such as 1000, 2500, 3000 or 27000.
[0011] The polyisocyanate may be an aromatic diisocyanate, such as diphenylmethane diisocyanate, toluene diisocyanate or isophorone diisocyanate.
[0012] The molar ratio of the polyol or polyamine to the polyisocyanate may be 1:(1-20), such as 1:(2-15).
[0013] According to an embodiment of the present invention, the mixing and reaction in steps 1) and 2) are carried out in a mixer, preferably in a mortar. Therefore, the mixing and reaction in steps 1) and 2) are preferably carried out by grinding.
[0014] According to a preferred embodiment of the present invention, the mixing in step 1) is carried out at 0-40°C, preferably 0-25°C, and the mixing time is more than 10 minutes, for example 10 minutes to 2 hours, such as 15 minutes to 1 hour; more preferably, the mixing in step 1) is carried out by grinding at 0-40°C, preferably 0-25°C.
[0015] According to an embodiment of the present invention, there is no particular limitation on the amount of monomer and positive electrode material used, provided that the coating amount of the polyurethane coating in the obtained positive electrode material is 0.1-5wt%; preferably 0.1-3wt%, more preferably 0.5-2wt%, most preferably 06-1.5wt%; for example 1wt%.
[0016] According to an embodiment of the present invention, a catalyst or an initiator may be added in step 2); or light, heat or radiation may be used to treat the raw materials in step 2).
[0017] According to an embodiment of the present invention, no solvent is used in steps 1) and 2).
[0018] According to an embodiment of the present invention, in step 2), the positive electrode active material is a ternary positive electrode material such as NCM, or lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, a lithium-rich manganese-based positive electrode material, preferably polycrystalline NCM622.
[0019] According to an embodiment of the present invention, in step 2), after mixing, the powder is ground under a baking lamp for more than 10 minutes, for example, 30 minutes.
[0020] According to an embodiment of the present invention, in step 2), after mixing, the powder may be heated at a temperature of 50°C or above, for example, 50-100°C.
[0021] The present invention also provides a positive electrode material prepared by the method as described above.
[0022] According to an embodiment of the present invention, the coating amount of the polyurethane coating in the positive electrode material is 0.1-5wt%, preferably 0.1-3wt%, more preferably 0.5-2wt%, most preferably 06-1.5wt%, for example 1wt%.
[0023] According to a preferred embodiment of the present invention, the positive electrode material is a coating structure formed by coating polyurethane prepared by reacting aminopropyl dicapped polydimethylsiloxane and toluene diisocyanate on polycrystalline NCM622 particles of the positive electrode material.
[0024] The present invention also provides use of the positive electrode material described above in preparing a lithium battery.
[0025] Beneficial effects of the present invention:
[0026] 1) The present invention adopts a solvent-free in-situ coating method. Since the selected polyurethane monomer can react quickly at room temperature, the preparation process is greatly simplified, and a good coating effect can be achieved. This method is not strict with the required monomers. Since it is a solvent-free coating method, the solvent volatilization and residual solvent waste in the traditional coating process will not be caused during the coating process, and it has a very good environmental protection effect. In addition, polyurethane itself has very good mechanical properties. Using polyurethane as a coating layer can just inhibit the volume expansion of the positive electrode active material and the harmful side reactions between the electrode and the electrolyte during the charging and discharging process of the lithium battery. In the structure of polyurethane, the silicon-oxygen segment has the characteristics of high voltage resistance and aging resistance, so that the positive electrode material after coating can have better cycle stability under high voltage or even other extreme conditions compared to traditional electrode materials. Compared with the traditional solvent coating method, the method of the present invention has the advantages of being environmentally friendly, low cost, wide source of raw materials, simple operation, suitable for large-scale industrial production, and easy to achieve commercialization.
[0027] 2) The structure of polyurethane has a very rich structural designability, which makes the coating layer have unlimited possibilities for improving performance. However, in the final analysis, for positive electrode materials, the improvement of the coating layer mainly lies in: (1) It can inhibit harmful side reactions between positive electrode materials and electrolytes, especially under high voltage or high temperature conditions; (2) It can slow down the stress expansion and breakage of positive electrode materials during charging and discharging; (3) It can act as a surface chemical modifier for ion charge transfer at the cathode / electrolyte interface and enhance the positive electrode / electrolyte interface transfer; (4) The coating material is cheap and easy to obtain, and the process is simple and environmentally friendly. Therefore, the use of polyurethane with structural design as a coating layer has a lot of room for optimizing the performance of positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a high-magnification scanning electron microscope photo of unmodified pure NCM622.
[0029] Figure 2 This is the specific capacity-voltage curve of the unmodified pure NCM622 assembled into a full battery in Example 1, activated at a cut-off voltage of 2.5-4.3V and a current density of 0.2C, and at a current density of 1C.
[0030] Figure 3 This is a schematic diagram of the long cycle performance test results of a full battery assembled from unmodified pure NCM622 in Example 1 at a cut-off voltage of 2.5-4.3V and a current density of 1C.
[0031] Figure 4 This is a high-magnification scanning microscope photograph of 1wt% coated NCM622 in Example 1.
[0032] Figure 5 This is the EDS element distribution diagram of 1wt% coated NCM622 in Example 1.
[0033] Figure 6 This is a transmission electron microscope photograph of the coating layer of 1wt% coated NCM622 in Example 1.
[0034] Figure 7 The specific capacity-voltage curve of a full battery assembled with 1 wt% coated NCM622 in Example 1 at a cut-off voltage of 2.5-4.3 V and activated at a current density of 0.2 C at a current density of 1 C.
[0035] Figure 8 It is a schematic diagram of the long cycle performance test results of a full battery assembled with 1wt% coated NCM622 in Example 1 at a cut-off voltage of 2.5-4.3V and a current density of 1C.
[0036] Fig. 9 This is a high-magnification scanning microscope photograph of 2wt% coated NCM622 in Example 2.
[0037] Fig.10 This is the EDS element distribution diagram of 2wt% coated NCM622 in Example 2.
[0038] Fig.11 It is a schematic diagram comparing the long cycle performance test results of 1wt% coated NCM622, 2wt% coated NCM622, 0.5wt% coated NCM622 and uncoated NCM622 assembled into full batteries at a cut-off voltage of 2.5-4.3V and a current density of 0.5C.
[0039] Fig.12 It is a full battery assembled from unmodified pure NCM622, activated at a current density of 0.2C at a cut-off voltage of 2.5-4.5V, and a specific capacity-voltage curve at a current density of 0.5C.
[0040] Fig.13 This is a schematic diagram of the long cycle performance test results of a full battery assembled from unmodified pure NCM622 at a cut-off voltage of 2.5-4.5V and a current density of 0.5C.
[0041] Fig.14 The specific capacity-voltage curve of the full battery assembled with 1wt% coated NCM622 in Example 1 at a cut-off voltage of 2.5-4.5V and activated at a current density of 0.2C at a current density of 0.5C.
[0042] Fig.15 It is a schematic diagram of the long cycle performance test results of a full battery assembled with 1wt% coated NCM622 in Example 1 at a cut-off voltage of 2.5-4.5V and a current density of 0.5C. DETAILED DESCRIPTION
[0043] The method of the present invention is described below by means of specific examples, but the present invention is not limited thereto, and any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention shall be included in the protection scope of the present invention. The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0044] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0045] Example 1
[0046] (I) Preparation of NCM622 positive electrode active material coated with 1wt% polyurethane
[0047] 1) Weigh two portions of 200 mg NCM622 and transfer them to two mortars respectively, then add 3.9 μL of aminopropyl di-terminated polydimethylsiloxane (molecular weight 3000) with a density of 0.98 g / mL and 1.5 μL of TDI (toluene diisocyanate) with a density of 1.225 g / mL to the two mortars respectively, and grind them evenly;
[0048] 2) Transfer all the NCM622 uniformly mixed with toluene diisocyanate to the mortar containing NCM622 with aminopropyl dimethylsiloxane, grind it quickly and thoroughly, and grind it for 15 minutes under the irradiation of a baking lamp. Finally, a polyurethane-coated NCM622 positive electrode active material is obtained.
[0049] Figure 4 This is a high-magnification scanning microscope photo of 1wt% coated NCM622 as above. Figure 4 The scanning electron micrographs show that polyurethane is coated on the NCM622 particles.
[0050] Figure 5 This is the EDS element distribution diagram of NCM622 coated with 1wt% as above. Figure 5 It can be seen that the Si element unique to the selected siloxane is evenly distributed on the surface of NCM622 particles.
[0051] Figure 6 This is a transmission electron microscope photo of the coating layer of 1wt% coated NCM622 as above. From the figure, it can be seen that on the surface of NCM622 particles, a coating layer with a thickness of 5-30nm can be seen on the particle surface.
[0052] (II) Assembly of full battery and its performance testing
[0053] The metal lithium sheet was used as the negative electrode of the full battery. The polyurethane-coated NCM622 positive electrode active material prepared in step (I) was taken, and the conductive carbon black Ketjen black was added. PVDF was used as the adhesive. The mass ratio of the polyurethane-coated NCM622 positive electrode active material: conductive carbon black: PVDF was 8:1:1 to prepare the slurry coating. The electrode sheet obtained by vacuum drying was used as the positive electrode. PP diaphragm, LiPF6 electrolyte containing 2% VC+EC / DEC / DMC mixed solvent, assembled to obtain a full battery. The surface capacity of NCM622 positive electrode material is 2.7mAh cm -2 The cut-off voltage of the test was about 2.5-4.3V, the test temperature was 25°C, the current density was 0.2C for five activation cycles, and the current density was 0.5C for cycling.
[0054] Figure 7 The charge and discharge curves are shown, and it can be seen that the charge and discharge reversibility is good and the polarization is small.
[0055] Figure 8 The reversible capacity of the full battery was shown to be cycled 200 times, and the capacity retention rate remained at 95.1%.
[0056] Example 2
[0057] The difference from Example 1 is that in step 1), 7.75 μL of aminopropyl dicapped polydimethylsiloxane with a density of 0.98 g / mL and 3 μL of toluene diisocyanate with a density of 1.225 g / mL were added to two mortars respectively. Fig. 9 From the scanning electron microscope photograph, it can be seen that there is an obvious coating layer on the surface of NCM622 particles coated with 2wt% polyurethane.
[0058] Fig.10 This is the EDS element distribution diagram of NCM622 particles coated with 2wt% polyurethane. It can be seen that Si is evenly distributed on the NCM622 particles.
[0059] Example 3
[0060] Referring to the methods of Examples 1 and 2, 0.5 wt% polyurethane-coated NCM622 particles were also prepared and assembled into a full battery.
[0061] from Fig.11 It can be seen that the full batteries assembled with 0.5wt% coated NCM622, 1wt% coated NCM622, and 2wt% coated NCM622 have a very obvious improvement in capacity retention rate compared with the original NCM622 after 500 reversible capacity cycles.
[0062] Figure 1 This is a high-magnification scanning electron microscope photo of pure NCM622. Figure 2 It is a full battery assembled from unmodified pure NCM622, activated at a cut-off voltage of 2.5-4.3V and a current density of 0.2C, and the specific capacity-voltage curve at a current density of 1C. Figure 3 This is a schematic diagram of the long cycle performance test results of a full battery assembled from unmodified pure NCM622 at a cut-off voltage of 2.5-4.3V and a current density of 1C. Fig.12 It is a full battery assembled from unmodified pure NCM622, activated at a current density of 0.2C at a cut-off voltage of 2.5-4.5V, and a specific capacity-voltage curve at a current density of 0.5C. Fig.13 This is a schematic diagram of the long cycle performance test results of a full battery assembled from unmodified pure NCM622 at a cut-off voltage of 2.5-4.5V and a current density of 0.5C.
[0063] from Fig.13It can be seen that the reversible capacity of the assembled full battery at a cut-off voltage of 2.5-4.5V is cycled for 240 cycles, and the capacity retention rate is only 44.82%. Because it has no polyurethane coating, during the cycle of the full battery, the positive electrode / electrolyte interface side reaction is accompanied by cation dissolution and cation mixing. At the same time, the volume expansion and fragmentation of NCM622 particles during the charge and discharge process result in a shorter cycle life than the positive electrode material coated with polyurethane coating.
[0064] From the above results, it can be seen that compared with the uncoated NCM622, when the polyurethane-coated NCM622 particles of the present application are used as positive electrode materials, the capacity retention rate of the assembled full battery is significantly improved when cycled at the conventional cut-off voltage of 2.5-4.3V, 1C high rate and 2.5-4.5V high voltage compared to the original NCM622, and the cycle is more stable, indicating that the polyurethane coating layer used in the present application on the surface of NCM622 can reduce the interfacial side reactions and volume expansion and particle breakage problems of the positive electrode material during the charging and discharging process, and stabilize the battery cycle.
[0065] Compared with the traditional coating method which usually needs to use solvent to disperse the polymer, the solvent-free in-situ coating method used in this application greatly reduces the impact of solvent on the environment and human body, while simplifying the process.
[0066] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for solvent-free in-situ coating of positive electrode materials, characterized in that: The steps include: 1) Grinding two monomers, polyol or polyamine and polyisocyanate, used to prepare polyurethane, with positive electrode particles respectively, so that the two monomers are distributed on the positive electrode material particles; 2) The positive electrode active material in which the two monomers are dispersed is mixed, so that the two monomers on the positive electrode material react with each other while adhering to the surface of the particles, thereby preparing a positive electrode material with a polyurethane coating.
2. The method according to claim 1, characterized in that Polyols or polyamines and polyisocyanates are monomers that can react at 0-40°C.
3. The method according to claim 1 or 2, characterized in that The polyol, polyamine and polyisocyanate have two or more functional groups.
4. The method according to any one of claims 1 to 3, characterized in that: The polyol and polyamine are polyols or polyamines having siloxane segments, including but not limited to at least one of bisamino-terminated siloxane, bisamino-terminated polysiloxane (e.g., aminopropyl bisamino-terminated polydimethylsiloxane), bishydroxy-terminated siloxane, and bishydroxy-terminated polysiloxane; and / or The polyisocyanate is an aromatic diisocyanate, such as diphenylmethane diisocyanate, toluene diisocyanate or isophorone diisocyanate.
5. The method according to any one of claims 1 to 4, characterized in that: The positive electrode active material is a ternary positive electrode material, lithium iron phosphate, lithium cobalt oxide, potassium manganate, preferably polycrystalline NCM622.
6. The method according to any one of claims 1 to 5, characterized in that: The mixing in steps 1) and 2) is carried out by grinding; Preferably, the mixing in step 1) is carried out at 0-40°C, preferably 0-25°C.
7. The method according to any one of claims 1 to 6, characterized in that: The mass ratio of the positive electrode material to the polyurethane is such that the coating amount of the polyurethane coating finally obtained for coating the positive electrode material is 0.1-5wt%, preferably 0.1-3wt%, more preferably 0.5-2wt%, most preferably 0.6-1.5wt%, for example 1wt%.
8. The method according to any one of claims 1 to 4, characterized in that: In step 1), the molar ratio of the polyol or polyamine to the polyisocyanate is 1:(1-20).
9. A positive electrode material prepared by the method according to any one of claims 1 to 8.
10. Use of the positive electrode material as claimed in claim 9 in preparing a lithium battery.